2020
DOI: 10.3389/fcell.2020.00669
|View full text |Cite
|
Sign up to set email alerts
|

Further Evidence That MicroRNAs Can Play a Role in Hemophilia A Disease Manifestation: F8 Gene Downregulation by miR-19b-3p and miR-186-5p

Abstract: Hemophilia A (HA) is a F8 gene mutational disorder resulting in deficiency or dysfunctional FVIII protein. However, surprisingly, in few cases, HA is manifested even without mutations in F8 . To understand this anomaly, we recently sequenced microRNAs (miRNAs) of two patients with mild and moderate HA with no F8 gene mutations and selected two highly expressing miRNAs, miR-374b-5p and miR-30c-5p, from the pool to explain the FVIII deficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…Thus, the interaction between non‐coding RNAs and F8 gene might represent an important path in understanding how patients without F8 mutations are lacking FVIII in blood and develop HA. It was shown that miR‐374b‐5p and miR‐30c‐5b target F8 gene and impair FVIII, indicating that classical HA could be evaluate not only by the mutational status 5,21 …”
Section: Resultsmentioning
confidence: 99%
“…Thus, the interaction between non‐coding RNAs and F8 gene might represent an important path in understanding how patients without F8 mutations are lacking FVIII in blood and develop HA. It was shown that miR‐374b‐5p and miR‐30c‐5b target F8 gene and impair FVIII, indicating that classical HA could be evaluate not only by the mutational status 5,21 …”
Section: Resultsmentioning
confidence: 99%
“…A recent report of HA in human patients who lack F8 mutations, showed that overexpression of miR-30c decreased FVIII expression, while a miR-30c inhibitor partially restored FVIII expression in two cell lines that constitutively express FVIII ( Jankowska et al, 2020a ). These findings led the authors to hypothesize that expression of miRNAs targeting the 3’-UTR of FVIII mRNA can modulate FVIII levels and may be responsible for a FVIII-deficiency phenotype that clinically manifests as HA ( Jankowska et al, 2020b ). Because KLF2 overexpression has been shown to induce upregulation of the miR-30 family members miR 30b and 30c ( Doebele et al, 2018 ), we next examined the levels of miR30c in PLC-mcoET3 in static vs. flow conditions and demonstrated that exposure to flow led to a nearly threefold induction of miR-30c in PLC-mcoET3, providing a mechanistic explanation for the differential response of the endogenous/native FVIII and the mcoET3 transgene to conditions of flow.…”
Section: Discussionmentioning
confidence: 99%
“…by targeting the factor VIII (FVIII), and miR-18a, miR-29a/b/c, miR-211, miR-193-3p, miR-186, etc. by targeting the fibrinogen (Fg) regulate the common coagulation pathway [202] , [203] , [204] , [205] ( Fig. 2 b-B1-3, 2b-D).…”
Section: Mirnasmentioning
confidence: 99%